Application of Inquiry Learning Model to Increase Motivation and Learning Outcomes of Grade IX Students at MTsN 3 West Aceh - Eddy N Mustika (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This study aims to obtain a description of teacher activity, in the process of this research is motivated by the low motivation and value of student learning outcomes, this is marked by 78.95% student scores still have not reached the minimum completeness criteria. This research is aimed at the use of the inquiry method in science grade IX-A learning on electromagnetic induction material. The research method used is classroom action research. The subjects of this study were 38 students of grade IX-A semester 2 MTsN 3 West Aceh, consisting of 16 male and 22 female students. Data collection techniques with tests, observation and documentation. The results of research using the inquiry method in the learning process increase the motivation and learning outcomes of students. The initial condition was 18% or 7 students increased to 21 students or 55% and reached 100% from 85%, and the increase in student learning outcomes from the average in the initial condition was 55.79, increasing to 65.79 in cycle I and on the end of the second cycle increased to 79.21 and completeness of learning in the initial conditions as many as 8 students (21.05%). Based on the results of the research, it can be concluded that learning using the inquiry method can improve the process, motivation and learning outcomes of grade IX-A students at MTsN 3 West Aceh Semester 2 Academic Year 2020/2021 on learning science with electromagnetic induction material.